FORMATION OF COLLOIDAL SILICA AND ALUMINA DURING EXPERIMENTAL GRANODIORITE WEATHERING - Faimon J. (My University, 2003)
The role of aluminum and silica in the formation of colloids during granodiorite weathering was studied on the basis of long-term experiments in batch reactors. Rock samples were dissolved in un-buffered solutions of initial pH ~ 3.2, 5.4, and 9.9 at ambient conditions for 500 days. During weathering, extremely high supersaturation with respect to various secondary solids was attained in the solutions. Consequently, new solids, part of which was conserved in solutions as colloids, condensed. The mean concentrations of colloidal Si reached values of 70, 50, and 48 μmol 1-1 in the alkaline, neutral, and acid solutions, respectively. The mean concentrations of colloidal Al, reached values of 34, 22, and 12 μmol 1-1 in the alkaline, neutral, and acid solutions, respectively. The concentration of colloids gradually decreased after 200-400 days of experiment. This phenomenon was interpreted as being due to the competition between homogeneous nucleation and crystal growth. At the initial stages of the experiments, the colloidal species (predominantly colloidal Al) comprised a large proportion of the total amounts of aqueous species. Their share, however, decreased with time. The molar Al/Si-ratios of colloids were as high as 2-2.5 at the early stages of the experiment. After 250-300 days of experiments, on the other hand, these ratios decreased to values of about 0.5 in both the neutral and alkaline solutions and to a value of 0.15 in the acid solution. The evolution of colloids was consistent with the evolution of secondary solids in the sequence Al-hydroxides - clay minerals (illite, chlorite), in both the neutral and alkaline solutions. In acid solutions, the evolution of Al/Si-colloids was influenced by the presence of sulfate ion and Al-sulfate precipitation. Besides Al and Si, other elements, in particular Ca or Mg as a major component and Na, K, P, S, and Cl as minor components, readily participated in the formation of colloids.
Keywords: ALUMINUM; COLLOIDS; DYNAMICS; GRANODIORITE; SILICA; SUPERSATURATION; WEATHERING